PERAN TATA USAHA DALAM ADMINISTRASI KURIKULUM - Sherlywaty Sherlywaty (UNIVERSITAS BENGKULU, 2020)
This research described the role of administration staff in curriculum administration at SMK Negeri 3 Seluma. Descriptive qualitative method was used in this study. The result of the research showed that the role of administration staff of SMK Negeri 3 Seluma in curriculum administration in planning, implementing, and evaluating aspects have been relevant with Permendikbud No. 24 Tahun 2008 about the standard of school administration staff.